Merger policy in digital markets: An ex-post assessment - Elena Argentesi; Paolo Buccirossi; Emilio Calvano; Tomaso Duso; Alessia Marrazzo; Salvatore Nava (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper presents a broad retrospective evaluation of mergers and merger decisions in the digital sector. We first discuss the most crucial features of digital markets such as network effects, multi-sidedness, big data, and rapid innovation that create important challenges for competition policy. We show that these features have been key determinants of the theories of harm in major merger cases in the past few years. We then analyse the characteristics of almost 300 acquisitions carried out by three major digital companies - Amazon, Facebook, and Google - between 2008 and 2018. We cluster target companies on their area of economic activity and show that they span a wide range of economic sectors. In most cases, their products and services appear to be complementary to those supplied by the acquirers. Moreover, target companies seem to be particularly young, being four-years-old or younger in nearly 60% of cases at the time of the acquisition. Finally, we examine two important merger cases, Facebook/Instagram and Google/Waze, providing a systematic assessment of the theories of harm considered by the UK competition authorities as well as evidence on the evolution of the market after the transactions were approved. We discuss whether the CAs performed complete and careful analyses to foresee the competitive consequences of the investigated mergers and whether a more effective merger control regime can be achieved within the current legal framework.
Keywords: L4; K21; 330; Digital Markets; Mergers; Network Effects; Big Data; Platforms; Ex-post; Antitrust